2018
DOI: 10.1080/15548627.2018.1489477
|View full text |Cite
|
Sign up to set email alerts
|

PTENα regulates mitophagy and maintains mitochondrial quality control

Abstract: BECN1 beclin 1; CCCP carbonyl cyanide m-chlorophenylhydrazone; FBXO7 F-box protein 7; FS fraction shortening; HSPA1L heat shock protein family A (Hsp70) member 1 like; HW: BW heart weight:body weight ratio; I-R ischemia-reperfusion; ISO isoprenaline; MAP1LC3/LC3 microtubule associated protein 1 light chain 3; MBH membrane binding helix; MFN1 mitofusin 1; MFN2 mitofusin 2; Nam nicotinamide; TMRM tetramethylrhodamine ethyl ester; WGA wheat germ agglutinin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 50 publications
0
53
0
Order By: Relevance
“…One last point to be mentioned is the role of phosphatase and tensin homolog (PTEN) itself, which seems to be directly involved in the modulation of mitophagy-related functions. Indeed a direct regulation of mitophagy through the promotion of Parkin recruitment to damaged mitochondria has been recently proposed for the first PTEN isoform identified so far, i.e., PTENα [77], whereas, interestingly, a newly identified long isoform of PTEN (PTEN-L) has been shown to act as a negative regulator of mitophagy by preventing Parkin mitochondrial translocation and inhibiting its E3 ligase activity [78]. Noteworthy, a fraction of PTEN has also been found to localize at the ER membrane and the MAMs and to regulate ER/mitochondria Ca 2+ transfer [79].…”
Section: The Pink1/parkin Pathwaymentioning
confidence: 99%
“…One last point to be mentioned is the role of phosphatase and tensin homolog (PTEN) itself, which seems to be directly involved in the modulation of mitophagy-related functions. Indeed a direct regulation of mitophagy through the promotion of Parkin recruitment to damaged mitochondria has been recently proposed for the first PTEN isoform identified so far, i.e., PTENα [77], whereas, interestingly, a newly identified long isoform of PTEN (PTEN-L) has been shown to act as a negative regulator of mitophagy by preventing Parkin mitochondrial translocation and inhibiting its E3 ligase activity [78]. Noteworthy, a fraction of PTEN has also been found to localize at the ER membrane and the MAMs and to regulate ER/mitochondria Ca 2+ transfer [79].…”
Section: The Pink1/parkin Pathwaymentioning
confidence: 99%
“…Moreover, it has been reported to play different roles at different stages of brain development, including neuron differentiation, migration, and synaptic plasticity modulation, mostly depending on its regulation on downstream target Akt (47,48). PTENa is recently shown to play a diversity of biologic roles in several recent studies, including regulation of mitochondria metabolism (21), regulation of spatial learning and contextual fear memory (22), cardiac homeostasis maintenance and regulation of mitophagy (23,24), and regulation of type I IFN responses and antiviral immunity (25). PTENa is expressed in many types of tissue, and expression of PTENa in the brain is high.…”
Section: Discussionmentioning
confidence: 99%
“…PTENa translates from the 59UTR region of the same mRNA as PTEN, containing an evolutionarily conserved 173-aa N-terminal extension (20,21). Recently, PTENa is shown to play important roles in maintenance of mitochondrial structure and energy metabolism (21), modulation of hippocampal long-term potentiation and processes of learning and memory (22), regulation of cardiac homeostasis and mitophagy (23,24), and promotion of type I IFN responses and antiviral immunity (25). However, it likely has other biologic functions that have not been characterized.…”
mentioning
confidence: 99%
“…Evidence suggests that decreased PINK1/Parkindependent mitophagy is associated with development of dystrophic cardiomyopathy (Kang et al, 2018). Recently, it has been reported that PINK1/Parkin-dependent mitophagy is regulated by several factors (Sun et al, 2014;Tahrir et al, 2017;Yu et al, 2017;Li G. et al, 2018;Pickles et al, 2018;Thai et al, 2018;Xiong et al, 2018;Ren J. et al, 2019;Shang et al, 2019). PTEN FIGURE 3 | Overview of mitochondrial biogenesis, fission and fusion in cardiomyocytes.…”
Section: Mitophagy In Cardiovascular Disease (Cvd) Pink1/parkin-depenmentioning
confidence: 99%
“…is a PIP3 phosphatase that generates phosphatidylinositol (4,5) bisphosphate (PIP2), which is involved in multiple biological processes. PTEN was reported to bind Parkin via a form of the membrane binding helix in N-terminus and enhance the recruitment of Parkin onto mitochondria, leading to the removal of damaged mitochondria and maintenance of cardiomyocyte homeostasis (Li G. et al, 2018). In addition, mitophagy in cardiomyocytes is regulated by mammalian Ste20-like kinase 1 (Mst1), which rapidly increases in cardiomyocytes upon LPS treatment or diabetic stress.…”
Section: Mitophagy In Cardiovascular Disease (Cvd) Pink1/parkin-depenmentioning
confidence: 99%